2004
DOI: 10.1116/1.1689296
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic vapor phase epitaxy of GaAs1−xNx alloy layers on GaAs(001): Nitrogen incorporation and lattice parameter variation

Abstract: Epitaxial GaAs1−xNx alloy layers, nominally 200-nm-thick, with x up to 0.0375 were grown on GaAs(001) at temperatures Ts varying from 500 to 650 °C to investigate nitrogen incorporation and lattice parameter variations during organometallic vapor phase epitaxy from trimethylgallium, tertiarybutylarsine, and 1,1-dimethylhydrazine. Quantitative secondary ion mass spectrometry measurements (SIMS) indicate that N incorporation decreases systematically with increasing Ts to become almost negligible at 650 °C. All f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 14 publications
1
27
0
Order By: Relevance
“…Combining HR-XRD and SIMS analysis revealed, as reported in Ref. [26], that the lattice constant decreases linearly with increasing x following closely the predictions of Vegard's rule for x up to 0.03. At higher nitrogen concentrations, the lattice constant decreases more rapidly as a significant fraction of N atoms becomes incorporated in non-substitutional sites as demonstrated by nuclear reaction analyses [26].…”
Section: Methodssupporting
confidence: 70%
See 2 more Smart Citations
“…Combining HR-XRD and SIMS analysis revealed, as reported in Ref. [26], that the lattice constant decreases linearly with increasing x following closely the predictions of Vegard's rule for x up to 0.03. At higher nitrogen concentrations, the lattice constant decreases more rapidly as a significant fraction of N atoms becomes incorporated in non-substitutional sites as demonstrated by nuclear reaction analyses [26].…”
Section: Methodssupporting
confidence: 70%
“…SIMS depth profiles also indicate that N concentrations remain constant as a function of depth in all layers with x up to 0.0375 [26].…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…12 As nitrogen is sensitive to nuclear reaction analysis (NRA), channeling NRA provided direct experimental evidence for the identification of such interstitial nitrogen. [13][14][15][16][17] Further study also revealed that the decrease of the interstitial N concentration induced by rapid thermal annealing could result in an increase in carrier concentration and mobility. 18 Compared with N-doped III-V HMAs, there is much poorer understanding of oxygen incorporation in II-VI alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial efforts have been made to investigate the location of nitrogen dopant in GaAsN HMAs. [12][13][14][15][16][17] In addition to substitutional placement, a considerable fraction of the nitrogen might present as N-N or N-As split interstitials. 12 As nitrogen is sensitive to nuclear reaction analysis (NRA), channeling NRA provided direct experimental evidence for the identification of such interstitial nitrogen.…”
Section: Introductionmentioning
confidence: 99%